Hydrogenation of levulinic acid to gamma-valerolactone over nickel supported organoclay catalyst - Kamble, Paresh A.; Vinod, C. P.; Rathod, Virendra K.; Kantam, Mannepalli Lakshmi (Catalysis Today, 2023)
In this work, a series of Ni/Organoclay catalysts with different Nickel loadings were prepared by the wetimpregnation method for the catalytic hydrogenation of levulinic acid (LA) to gamma-valerolactone (GVL). Reaction parameters such as reaction temperature, pressure, solvent effect, and wt% of catalyst were optimized to get excellent conversion of levulinic acid selectively to gamma-valerolactone. Ni/Organoclay with 30% Nickel loading exhibited 100% conversion of LA with 100% selectivity towards GVL at 140 degrees C and 3.0 MPa H2 pressure using 1,4-dioxane as a solvent in 5 h. Different bulk and surface characterization techniques such as XRD, BET, FE-SEM, HR-TEM, XPS, XRF, NH3-TPD, and H2-Chemisorption were used to characterize the Ni/Organoclay catalyst. BET and NH3-TPD analysis showed that the pre-treatment of bentonite with surfactant (CTAB) improved the pore volume, surface area, and acidity of Organoclay which assisted in improving the conversion and selectivity of LA and GVL respectively.
Keywords: ?-Valerolactone (GVL); Bentonite; Hydrogenation; Levulinic acid (LA); Nickel; organoclay

Imine oxidation catalyzed by zinc hydroxyapatite: kinetic studies - Vishwakarma, Rakhi; Vinod, C. P.; Rathod, Virendra K.; Kantam, Mannepalli Lakshmi (ChemistrySelect, 2023)
The synthesis of N,N-diphenylformamide from N-benzylideneaniline and urea hydrogen peroxide is investigated using a zinc hydroxyapatite (ZnHAP) catalyst. It was found that the catalyst resulted in the highest activity of 91 % conversion and 40 % selectivity at 130 degrees C in 2 h. A kinetic model was validated by Langmuir-Hinshelwood-Hougen-Watson (LHHW) at different temperatures and the absence of mass transfer resistance was proved by the Weisz Prater criterion. Effect of different catalysts, catalyst loading, temperature, mole-ratio, and speed of stirring was studied. The as-synthesized catalyst is characterized by FTIR, BET nitrogen adsorption-desorption, TEM, EDX, TPD-NH3, XPS, ICP-MS and XRD. ZnHAP catalyst was found to be stable up to three recycles with no loss in activity.
Keywords: heterogeneous catalysis; hydroxyapatite; imines; Oxidation; Reaction kinetics

Hydrogenation of furfural to tetrahydrofurfuryl alcohol over nickel-supported on organoclay catalyst - Kamble, Paresh A.; Vinod, C. P.; Rathod, Virendra K.; Kantam, Mannepalli Lakshmi (Applied Catalysis A-General, 2024)
Nickel supported on organoclay prepared by the impregnation method provides excellent catalytic activity for the hydrogenation of furfural to tetrahydrofurfuryl alcohol. The relative amount of metal and acidic sites influences the hydrogenation reaction. Additionally, by varying the temperature and the H-2 pressure, we can regulate the interaction of furfural with the active sites. And this may decide the fate of the reaction whether it will undergo a two-step hydrogenation to form tetrahydrofurfuryl alcohol or a rearrangement reaction to form cyclopentanone/cyclopentanol. Water was found to be the best solvent for the selective formation of tetrahydrofurfuryl alcohol. Even though alcohols inhibited rearrangement reaction, the hydrogenation of furfural was more selective towards furfuryl alcohol. Ni/O-clay30A under the optimum conditions of 120 degrees C, 4.0 MPa, and in 1 h offered complete conversion of furfural to tetrahydrofurfuryl alcohol.
Keywords: furfural; Hydrogenation; Nickel; organoclay; Tetrahydrofurfuryl alcohol

Hydrogenation of glucose to sorbitol by using nickel hydroxyapatite catalyst - Kamble, Paresh A.; Vinod, Chathakudath P.; Rathod, Virendra K.; Lakshmi Kantam, Mannepalli (Chemcatchem, 2024)
A series of nickel hydroxyapatite catalysts were synthesized by the co-precipitation method followed by calcination and reduction. These catalysts were employed for the aqueous phase hydrogenation of glucose to sorbitol. The Ni-HAP catalyst with comparatively high surface area and acid-base strength gave high sorbitol selectivity in 1 h. Ni-HAP-4 catalyst with moderate Ni (3.5 wt. %) content having smaller and highly dispersed nickel particles gives an excellent yield of sorbitol, 97 % in 1 h. The Ni-HAP-4 catalyst works well with other polar protic solvents. Different characterization techniques like XRD, TEM, SEM-EDS, BET, NH3-TPD, and CO2-TPD were employed to analyze the Ni-HAP-4 catalyst. A facile hydrogenation of glucose to sorbitol has been reported with Ni-HAP catalyst using water as a solvent. The excellent yield of sorbitol, 97 % in 1 h is possible due to the high surface area and high acid-base strength of the Ni-HAP-4 catalyst. image
Keywords: glucose; Hydrogenation; Hydroxyapatite (HAP); Nickel; Sorbitol

Synthesis of 5-hydroxymethylfurfural from glucose using a tert-butoxyapatite catalyst - Kulkarni, Hemant S.; Kamble, Paresh A.; Vinod, Chathakudath P.; Rathod, Virendra K.; Kantam, Mannepalli Lakshmi (DALTON TRANSACTIONS, 2025)
In this study, 5-hydroxymethylfurfural (5-HMF) was obtained from glucose using tert-butoxyapatite, a heterogeneous catalyst. The tert-butoxyapatite catalyst was prepared and characterized by several techniques, such as XRD, SEM, TEM, EDS, elemental mapping HR-TEM, N2-adsorption/desorption, XPS, and FT-IR. Several parameters were studied, such as temperature, catalyst loading, and glucose concentration. The tert-butoxyapatite catalyst having both acidic and basic sites gave a maximum glucose conversion of 87% with a 48% yield of HMF at 160 degrees C using 20 wt% catalyst in 12 h. Reusability studies of the catalyst are also presented.